Galectin 3: an extraordinary multifunctional protein in dermatology. Current knowledge and perspectives - Efstathia Pasmatzi; Christina Papadionysiou; Alexandra Monastirli; George Badavanis; Dionysios Tsambaos (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Galectin 3 is a unique ~31 kDa protein that recognizes the N-acetyl-lactosamine structure of several glycoconjugates. It mainly occurs in epithelial and myeloid cells, but is also found in a variety of human cell types. In view of the crucial role played by galectin 3 in the regulation of cellular processes of essential importance and in the pathogenetic mechanisms of diverse disorders, it is not surprising that, particularly in the last three decades, the attention of the scientific community has been increasingly drawn to this extraordinary and multifunctional galectin. In this paper the authors summarize current knowledge on the expression of galectin 3 in normal and diseased human skin, its implications in the pathogenesis, diagnosis and prognosis of cutaneous disorders, and the perspectives of a novel approach to the treatment of the latter using galectin 3 or its inhibitors/antagonists.